Análise dialélica, parâmetros genéticos e índice de seleção em populações segregantes de soja - Silva, Lorrayne Lucinda (2021)
Knowing about the progenies that will be used during the genetic improvement process makes it possible to carry out a more assertive selection, which results in saving time and resources that can be allocated to superior progenies. This dissertation was divided into three chapters. The first chapter deals with the theoretical framework, which addresses aspects of soybean culture in general, genetic improvement, diallel analysis, and the genetic parameters of the culture as well as selection indices. The second chapter aimed to determine the general and specific capacity of combinations of soybean genotypes regarding agronomic attributes, in order to identify parents and hybrid combinations promising for soybean breeding. The experiments were carried out in the Soybean Genetic Improvement Program at UFU, in Uberlândia – MG. Five parents were sown in a greenhouse UFUS Xavante, UFUS Guará, UFUS 7101 and TMG 801 and six resulting F1 hybrids resulting from the crosses. The number of days to flowering and maturity, height of insertion of the first pod, number of nodes, number of pods per plant and grain yield per plant were evaluated. Cultivars UFUS Xavante, UFUS Guará and UFUS 7101 contributed to a decrease in the number of days for flowering and maturity and for grain weight. The hybrid combinations UFUS Guará x UFUS 7101 and UFUS Xavante x UFUS Guará demonstrated that it has the capacity to obtain segregating populations with a shorter cycle and with high production. In the third chapter, the objectives were to know the genetic parameters and selection gains of agronomic traits and to select F4:5 and F5:6 soybean progenies sown in two different crops through selection indices. The number of days for flowering and maturity, height of insertion of the first pod, number of nodes, number of pods per plant and grain weight were evaluated for the first crop. For the second crop, the number of days to flowering and maturity was evaluated, as well as the grain weight. The segregating populations F4:5 and F5:6 showed high genetic potential and allow the application of different selection methodologies in the search for superior progenies. The direct selection of the character APF, APM and AIPV is indicated for indirect selection for the other characters, for the 2019/20 harvest and jointly with the 2020/21 harvest. Progenies UFUS_182 E2B1 A91P2, UFUS_14 E1B1 A29P2, UFUS_81 E1B3 A145P1, UFUS_202 E3B2 F3C363, UFUS_ 157 E3B3 PB17, UFUS_ 157 E3B3 PB17, UFUS_21 E1B1A35P1, UFUS_176 E1B3 A27P2, UFUS_179E3B2 F3C291, UFUS_79 E1B3 A145P1, UFUS_43 E1B2 A146P1, UFUS_177 E1B3 A27P2, UFUS_109 E2B2 F3A183 were selected by both selection indexes, in the joint analysis.